Implication of reporting and governance framework in waqf institution: A case study of Perbadanan Wakaf Selangor (PWS) - Muhammad Syazwan, Nadzri (2024)
The mutawalli, or waqf manager, plays a critical role in fostering public trust, which is essential for the effective management of waqf assets. This study explores the implications of governance and reporting frameworks within waqf institutions in Malaysia, with a specific focus on Perbadanan Wakaf Selangor (PWS). It addresses inefficiencies in governance and reporting practices that impede the effective administration of waqf funds. Using a qualitative methodology, the research employs semi-structured interviews with mutawalli to gain in-depth insights into their experiences and perceptions. The study investigates key variables, including the effectiveness of governance frameworks, the importance of reporting standards, and mutawalli perceptions of their influence on operational efficiency and public trust. Findings reveal significant gaps in existing governance structures and reporting standards, highlighting how the absence of a structured framework negatively impacts transparency and accountability in waqf institutions. These deficiencies hinder efficient management and diminish public confidence. Additionally, the research demonstrates that adherence to standardized reporting and governance practices enhances stakeholder confidence by enabling better evaluation and comparison of waqf institution performance. Interviewee responses indicate that increased transparency and accountability not only improve decision-making processes but also reinforce public trust. This study contributes to the discourse on improving waqf governance by identifying critical areas for reform. It offers policy recommendations to strengthen governance and reporting practices, aiming to enhance operational efficiency and reinforce the role of waqf institutions in community development and social welfare. By advocating for the adoption of structured frameworks, the research underscores the potential for waqf institutions to achieve greater sustainability and effectiveness, ultimately fulfilling their objectives of serving societal needs and fostering socio-economic development.